2020
DOI: 10.1111/jdv.16325
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis fungoides: developments in incidence, treatment and survival

Abstract: Background Prior studies have demonstrated improved disease-specific survival of mycosis fungoides (MF) patients over the last 50 years. Objective To analyse patterns of survival and incidence from 1973 to 2016 and determine whether apparent improvements in MF-specific survival are due to lead-time bias rather than improvements in treatment. Methods We performed an analysis of 10 155 patients diagnosed with MF from 1973 to 2016 in the United States cancer registries of SEER-18. We also performed a literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
0
32
0
3
Order By: Relevance
“…Mycosis fungoides (MF), characterized by a monoclonal proliferation of CD4‐positive T cells, is the most common type of cutaneous T‐cell lymphoma (CTCL) and constitutes almost 50% of all primary cutaneous lymphomas. 1 According to a newly published study, the incidence of MF increased from 3.0 per million person‐years in the 1970s to 5.9 in the 2010s, 2 with a higher incidence in Blacks. 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycosis fungoides (MF), characterized by a monoclonal proliferation of CD4‐positive T cells, is the most common type of cutaneous T‐cell lymphoma (CTCL) and constitutes almost 50% of all primary cutaneous lymphomas. 1 According to a newly published study, the incidence of MF increased from 3.0 per million person‐years in the 1970s to 5.9 in the 2010s, 2 with a higher incidence in Blacks. 3 …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the survival rates are associated with the stages and patients presenting with an early stage at diagnosis have a better prognosis. 2 , 8 , 9 , 10 Therefore, early diagnosis is essential to improve the prognosis of patients with MF.…”
Section: Introductionmentioning
confidence: 99%
“…Mycoses fungoides is a rare cutaneous lymphoma, and even fewer cases are present in its purpuric variant (PMF) 13 . Some authors have suggested that PPD may precede mycosis fungoides over the years 7,14 ; nevertheless, mycosis fungoides may initially manifest with purpuric eruptions as in PMF 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Mycoses fungoides is a rare cutaneous lymphoma, and even fewer cases are present in its purpuric variant (PMF). 13 Some authors have suggested that PPD may precede mycosis fungoides over the years 7,14 ; nevertheless, mycosis fungoides may initially manifest with purpuric eruptions as in PMF. 15 Clinical and histopathological features of PPD and PMF mimic each other considerably and make the differentiation of these entities challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal T-cell receptor (TCR) gamma gene rearrangements, that may be determined by PCR-based amplification and gel electrophoresis, support the diagnosis [ 2 ]. MF usually follows an indolent course but may progress from a patch stage to plaque to tumor and disseminated disease [ 3 ]. There is generally good clinicopathologic correlation for these stages of disease and they display distinct findings histologically [ 4 ].…”
Section: Introductionmentioning
confidence: 99%